If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = 3x + -2 Reorder the terms: 2x = -2 + 3x Solving 2x = -2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2x + -3x = -2 + 3x + -3x Combine like terms: 2x + -3x = -1x -1x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 -1x = -2 + 0 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| 502.4=12(3.141592654)(r)+(3.141592654)(r^2) | | 4p^2q+q^3-q^2=0 | | 502.4=12(pi)(r)+(pi)(r^2) | | 4-2n=5n+n | | 33=P(0.06)3 | | 6+2n=4n-3n | | 8v+1=7v-2-0 | | 9-(4y-9)=8-5y | | -21c+19=21c-1 | | -36+3x^2=0 | | 3x^2*x=108 | | 18=15-n+3 | | 0.5(6x+12)=1.3-(x+2) | | 6x-y=17 | | 2-2n=n+15 | | -20=10-6+n | | -16=5+n | | 6(3-2z)+13z-4= | | 4+3n=1-4n | | 36+p-4=p | | 3x-9=x+4 | | v(v+1)=272 | | 2-8v=2v+8 | | =6x^2+5xy-25y^2 | | 5m+1=3m+9 | | v(v+1)=132 | | 4t+20=15 | | 5p=1-21 | | 3n=6+15 | | -13j(4j-32)=507 | | -n-3n= | | 35k^2-22k-3=0 |